Coach Training Within the Covid-19 Pandemic: Challenges and Potential Pathways - Santos, Fernando; Cardoso, António; Pereira, Paulo; Strachan, Leisha (Frontiers in Psychology, 2021)
In this article we aim to provide insights about the challenges stakeholders in Portugal and across the globe may face throughout the Coronavirus Disease 2019 pandemic to reorganize coach training programs and suggest strategies to help coaches learn. Such reflection may help stakeholders across socio-cultural contexts consider the consequences of the changes made to coach training programs, the rationale for these decisions and the need to acknowledge existent challenges such as lower course completion rates, pressures to deliver the curriculum and dilemmatic decisions about course format. Furthermore, we also suggest pathways for stakeholders to develop strategies that consider contextual variables and contribute to meaningful learning. Based on the Portuguese context, several issues are discussed.